PENGARUH STRUKTUR MODAL DAN LIKUIDITAS TERHADAP PROFITABILITAS - Bunga Asri Novita; Sofie Sofie (Jurnal Akuntansi Trisakti, 2015)
This object of this study is analyze the impact of capital structure and liquidityon profitability. The sample used in this study is the beverages, food, and tobaccosector companies listed in Indonesia Stock Exchange between 2009 and 2013. Theindependent variables are the capital structure and liquidity, while the dependentvariable is profitability. Total sample is 19 companies. The results of this study indicate that the capital structure and liquidity together have significant effect on profitability. Based on these results, the expected managerial pay more attention to the structure of capital and liquidity in order to increase the profitability of the companies.